Involvement of the endocannabinoid system in reward processing in the human brain - van Hell, Hendrika H. (Springer-Verlag, 2011)
RATIONALE: Disturbed reward processing in humans has been associated with a number of disorders, such as depression, addiction, and attention-deficit hyperactivity disorder. The endocannabinoid (eCB) system has been implicated in reward processing in animals, but in humans, the relation between eCB functioning and reward is less clear. OBJECTIVES: The current study uses functional magnetic resonance imaging (fMRI) to investigate the role of the eCB system in reward processing in humans by examining the effect of the eCB agonist Δ(9)-tetrahydrocannabinol (THC) on reward-related brain activity. METHODS: Eleven healthy males participated in a randomized placebo-controlled pharmacological fMRI study with administration of THC to challenge the eCB system. We compared anticipatory and feedback-related brain activity after placebo and THC, using a monetary incentive delay task. In this task, subjects are notified before each trial whether a correct response is rewarded (“reward trial”) or not (“neutral trial”). RESULTS: Subjects showed faster reaction times during reward trials compared to neutral trials, and this effect was not altered by THC. THC induced a widespread attenuation of the brain response to feedback in reward trials but not in neutral trials. Anticipatory brain activity was not affected. CONCLUSIONS: These results suggest a role for the eCB system in the appreciation of rewards. The involvement of the eCB system in feedback processing may be relevant for disorders in which appreciation of natural rewards may be affected such as addiction. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00213-011-2428-8) contains supplementary material, which is available to authorized users.